E-Business Adoption among Women-Owned Small and Medium-Sized Enterprises in Malaysia: A Conceptual Perspective - Yeong, Yen Nee; Hanifah, Haniruzila; Abdul Halim, Hasliza; Kartika Dewi, Yuli (Journal of Technology Management and Business, 2022)
This conceptual study examines relative advantage, compatibility, and complexity as technological drivers of e-business adoption among women-owned small and medium-sized enterprises (WOSMEs) in Malaysia. The mediating effect of e-business adoption between the technological variables and WOSME performance is also discussed. Literature on the technological factors of e-business adoption is reviewed and classified to develop an extended conceptual framework. The conceptual framework serves as a foundation for future empirical research and offers practitioners insights into the benefits of e-business adoption for WOSMEs in Malaysia. Specifically, e-business adoption can secure competitive advantages in terms of efficiency, sales performance, customer satisfaction, and relationship development. Even though this study presented the fundamental conceptual framework to comprehend e-business adoption among WOSMEs in Malaysia, future research offers a huge possibility to expand the framework and explain the key constructs' roles in determining performance.